LOS TABERNÁCULOS DEL BARROCO ANDALÚZ - Rivas Carmona, Jesús (Imafronte, 1989)
One of the most interesring chapters in the baroque retable-making activity in Andalusia is presetired by the rich series of isolated tabernacles or templetes [litle temples]. They stand out both because of the privileged location on the heads of cathedrals and collegial churches and their specialfunction, the Eucharistic exhibition, which distinguish these Andalusian structures from other Spanish ones, usually reserved to Saints. It justifies the name tabernaclen itself: After Diego de Siloe arranged un isolared tabernacle in the rotunda in the cathedral of Granada, this type of altar became in fashion in Andalusia, particularly in eastern Andalusia, and examples as inreresring as St. Sebastian, in Anrequera or those of the Grace Trinnitarians and Santo Domingo, in Granada, were erected along the XVIIIth century the later two are made in polycrhome marbles). Hurtado Izquierdo starts from them to reach the most original and very baroque solutions in the first decades of the XVIIIth century. His works will inspire well known artists, like José de Bada and Pedro Duque Corriejo.